2004
DOI: 10.1002/bem.20050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in vitro exposure to power frequency magnetic fields on UV‐induced DNA damage of rat lymphocytes

Abstract: The mechanisms of biological effects of 50/60 Hz (power frequency) magnetic fields (MF) are still poorly understood. There are a number of studies indicating that MF affect biochemical processes in which free radicals are involved, such as the biological objects' response to ultraviolet radiation (UVA). Therefore, the present study was aimed to assess the effect of 50 Hz MFs on the oxidative deterioration of DNA in rat lymphocytes irradiated in vitro by UVA. UVA radiation (150 J/m2) was applied for 5 min for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Also, it has been reported that ELF MF could potentiate the DNA damage induced by H 2 O 2 (74) or influence the radical pairs generation during the oxidative or enzymatic processes of DNA repair (75). Herein reported results show that a 42-h exposure to MF potentiates the ROL-induced stimulation of DNA replication and cell growth in NB69 cells.…”
Section: Discussionmentioning
confidence: 53%
“…Also, it has been reported that ELF MF could potentiate the DNA damage induced by H 2 O 2 (74) or influence the radical pairs generation during the oxidative or enzymatic processes of DNA repair (75). Herein reported results show that a 42-h exposure to MF potentiates the ROL-induced stimulation of DNA replication and cell growth in NB69 cells.…”
Section: Discussionmentioning
confidence: 53%
“…Nindl et al [] studied the effect of simultaneous exposure to a magnetic field at 1 mT and 100 Hz and UV‐B followed by magnetic field exposure alone against DNA synthesis and repair in Jurkat cell, and reported that the magnetic field enhanced the lymphocyte cell killing effect. Zmyślony et al [] investigated the potential interaction between the magnetic field at 40 µT and 50 Hz and UV‐A in rat lymphocytes, and reported that the magnetic field exposure significantly enhanced the damage induced by UV‐A irradiation. The exposure to a magnetic field and UV‐A was started simultaneously, but UV‐A irradiation was ended after 5 min and the magnetic field was continued for 60 min.…”
Section: Discussionmentioning
confidence: 99%
“…Within the range of household frequency that we tested (50/60 Hz), some studies find no evidence for cell stress in bacteria [Nakasono and Saiki, 2000] or human cells [Coulton et al, 2004]. Others provide evidence that MF causes cellular damage [Zmyslony et al, 2004], and/or expression of stress-responsive proteins [Lin et al, 1997;Cairo et al, 1998;Goodman and Blank, 2002;Robison et al, 2002;Tokalov and Gutzeit, 2004] which serve as biological markers of cell stress. Cells respond to harsh physiological conditions by inducing the expression of protective stress proteins like heat-shock proteins.…”
Section: Mf-induced Secondary Cross-stress Protection In the Viabilitmentioning
confidence: 96%